Asuhan Keperawatan pada Keluarga Tn. T dengan Gangguan Sistem Kardiovaskular: Hipertensi di Desa Kalibuntu RT 02 RW 02 Kecamatan Losari Kabupaten Brebes - Muhamad Afrizal; Tati Karyawati; Arisnawati Arisnawati (NAJ Nursing Applied Journal, 2024)
Hypertension is a condition where there is an abnormal and continuous increase in blood pressure caused by one or several risk factors that do not work as they should in maintaining normal blood pressure (Majid, 2018). The signs and symptoms in hypertensive patients are the onset of pain. due to increased blood pressure. The purpose of this writing is to find out and provide nursing care to Mr. T With Cardiovascular System Disorders: Hypertension in Kalibuntu Village Rt 02 Rw 02 Losari District, Brebes Regency in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that Mr. T complains of pain. There were two diagnoses found, namely acute pain and knowledge deficit. Interventions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.